Measuring the Competitive Advantage of Countries Along the Belt and Road From the Perspective of Complex Social Networks - Wang, Yanni; Chen, Wen; Jiang, Chuke; Xing, Lizhi (Frontiers in Physics, 2022)
For the Belt and Road Initiative, “extensive consultation, joint contribution, and shared benefits” is the basic principle, and competitiveness heterogeneity is an important condition for cooperation. Based on the complex network theory, this paper constructs a complex network model of global value chain (GVC) division of labor system by using the Inter-Country Input-output (ICIO) table and reveals the variation trend of competitiveness of industrial sectors and economies on the GVC network by the National Competitive Advantage Index (NCAI). The results verify the effectiveness of BRI, and help countries along the BRI route to explore their comparative advantages and cooperation prospects with other countries. The research also provides a direction and reference for China to better implement the Initiative.